Effect of manual therapy on music students with playing-related musculoskeletal disorders: a prospective study - Assel, Carolin; Nugraha, Boya; Kallusky, Nicolas; Faßnacht-Lenz, Stephan; Altenmüller, Eckart; Gutenbrunner, Christoph; Sturm, Christian (Frontiers in Pain Research, 2023)
Playing Related Musculoskeletal Disorders (PRMD) belong to the most prevalent medical ailments affecting musicians' health and career. This study documents the effect of a physiotherapeutic treatment as well as functional impairments of PRMD on the musculoskeletal system. In total, 32 music students suffering from PRMD were examined in Hanover Medical School (MHH) before and after they received twelve physiotherapeutic treatments, which were carried out over 20 min each over 6 weeks. Additionally, 32 healthy music students, matched by age and gender, were examined at one time point in the MHH to explore which musculoskeletal restrictions are associated with PRMD. The examination included the evaluation of the pain on the Visual Analogue Scale for pain (VAS), a body composition, and body posture measurement, the finger-to-floor distance, the range of motion of the cervical spine, the pressure pain and muscular hypertension examination, the temporomandibular joint-test, the Beighton score screening test, and the testing of the widespread pain score (WSP). After analyzing the data of the patient group (PG) a significant reduction of pain level on the VAS from an average pain of 5.33 to 3.35 was found (large effect). Additionally, a significant reduction of the pressure pain of the M. levator scapulae, the M. rhomboideus, the M. sternocleidomastoideus on the left side and the paravertebral muscles of the cervical spine on the right side after the treatment of the patients could be detected. Regarding the WSP, the positive testing significantly differed, showing a 28% positive testing in the patient group vs. a positive testing of 9% in the control group (CG). As hypermobility is a common phenomenon in musicians, the percentage of those being diagnosed with generalized hypermobility by using the Beighton score in both groups (PG: 37.5%; CG: 25%) was remarkably higher compared to previous studies. In this study, a short course of manual therapy, client tailored for each musician's specific problem, was shown to reduce pain levels in musicians with PRMD.